UNDERGRADUATE CURRICULUM STUDY. - Black, Martin L.; Claire, Richard; Johnson, Arnold W.; Mikesell, R.M.; Morrison, Lloyd F.; Van Voorhis, R.H.; Wixon, Rufus (The Accounting Review, 1956)
Abstract This article presents a report of the Task Committee, American Accounting Association on the standards of accounting instruction. From its inception, the American Accounting Association has been concerned with accounting education. This interest has been manifested in various projects and special committee activities undertaken by the Association, alone and jointly with other groups. One of the Association's special task committee in the area of education is the Committee on Standards of Accounting Instruction. It operates in cooperation with, and as a task force of, the Joint Committee on Education. The first project of the Committee on Standards of Accounting Instruction was a questionnaire study of the undergraduate courses taken by accounting majors. The questionnaire was carefully prepared and tested before being released. It was sent to most of the colleges and universities in the U.S. , which offered a major or concentration in accounting in an undergraduate program. The study indicated that the largest school in the sample graduated 837 students in 1954 with bachelor degrees in business. It was notable that 1954 saw less than half as many accounting majors graduating as in 1950. The decline in degrees in business was considerably sharper than for all bachelor degrees. The Committee felt that course work in cost accounting is properly required by nearly all schools